PFAS perfluorinated organic compounds – a new challenge in preparing water for consumpti - Włodarczyk-Makuła, Maria; Zimoch, Izabela (Instal, 2024)
The aim of the article was a general characterization of organic micropollutants from the group of perfluorinated surfactants (PFAS) in the context of proposed changes in legal regulations regarding drinking water. These changes are necessary due to the inclusion of PFAS in the Water Directive on the list of compounds whose control in drinking water will be required and monitored. The PFAS group includes several thousand compounds in the structure of which fluorine is attached instead of hydrogen to a chain (straight or branched) of aliphatic hydrocarbons. Determining the concentrations of these compounds in water will be a challenge for water supply companies due to analytical difficulties. Due to the presence of these compounds in surface and groundwater, which is the source of drinking water for the population, it will be necessary to include them in ongoing monitoring. This is important for the health of the population due to the potentially toxic effects of these compounds. The article describes the properties of perfluorinated compounds, their impact on organisms, the permissible concentrations of PFAS in drinking water specified in legal regulations in other countries, and the analytical methodology of these compounds.
Keywords: PFAS; surfactants; drinking water; legislation; chromatographic method